Adipose-derived stem cells modulate neuroinflammation and improve functional recovery in chronic constriction injury of the rat sciatic nerve - Chen, Szu-Han; Wu, Chia-Ching; Tseng, Wan-Ling; Lu, Fu-I; Liu, Ya-Hsin; Lin, Shau-Ping; Lin, Sheng-Che; Hsueh, Yuan-Yu (Frontiers in Neuroscience, 2023)
Compressive neuropathy is a common type of chronic traumatic injury of the peripheral nerves with variable degrees of sensory and motor function impairment. The clinical symptoms do not fully resolve after decompression, with 10%–25% of patients suffering from muscle atrophy and persistent neuropathic pain. Sustained immune cell infiltration and excessive inflammation within the injured nerve further impede axon regeneration and functional recovery. Adipose-derived stem cells (ASCs) have shown great potential for neural regeneration and immunomodulation, but their beneficial effects on compressive neuropathy remain unclear. In this study, persistent neuropathic pain was induced by chronic constriction of the rat sciatic nerve. Local ASC treatment has demonstrated robust beneficial outcomes, including the alleviation of mechanical allodynia, improvement of gait, regeneration of muscle fibers, and electrophysiological recovery. In addition, locally transplanted ASCs facilitated axon remyelination, alleviated neuroinflammation, and reduced inflammatory cell infiltration of the injured nerve and associated dorsal root ganglion (DRG). Tracking of the transplanted ASC showed preserved in vivo viability and phenotype and contribution to immunomodulatory regulation of inflammatory gene expression in the injured nerve and DRG, suggesting a promising role for adjuvant ASC therapies in clinical compressive neuropathy.